After Socrates ”“ A Trilogy: (i) Remembering Socrates - Cecílio, Guilherme da Costa Assunção; Martins, Mariana Machado Rodrigues e Silva (Revista Archai, 2018)
After Socrates ”“ A Trilogy: (i) Remembering Socrates